Synthesis, Structural, Morphological Characterization, and Cytotoxicity Assays of Metal Complexes Decorated SiO2 Nanoparticles Against Breast Cancer Cell Lines (MDA-MB-231) - Alya'a J. Ahmed; Mahasin F. Alias (مجلة بغداد للعلوم)
This study examines the new synthesis of Pt (IV) and Au (III) Mannich base complexes derived from ciprofloxacin. The complexes were then used as precursors to prepare SiO2/PtO2 and SiO2/Au2O3 nanoparticles by depositing the synthesized complexes on porous silica nanoparticles. Elemental analysis, FT-IR, UV-vis, molar conductivity measurements, and melting point were used to characterize this ligand and its metal complexes. Elemental analysis data show that the general formula of the metal complexes formed is [M(L)2Cl2] nCl.H2O, where L = Mannich base ligand and M = Au(III) and Pt(IV), and n = 1,2 respectively with octahedral structure. The chemical structure and morphology of the metal oxide nanoparticles are investigated using FT-IR, XRD, AFM, TEM, and SEM. In the next step, the ligand and its complexes, SiO2/PtO2 and SiO2/Au2O3 nanoparticles were examined to investigate their toxicity (in vitro) as an anticancer agent to MDA-MB-231 cell lines by using different concentrations (50, 100, 200, and 400 µg /mL). Based on the results obtained from the cytotoxic activity, it can be concluded that the synthesized compounds are promising as new cancer candidates in the future, especially in high concentrations